THE NATIONAL INTEREST OF RUSSIA IN BUILDING NATION BRANDING THROUGH ORGANIZING THE 2018 WORLD CUP - Tambun, Nazaretha; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research describes Russia's interest in the 2018 FIFA World Cup. The World Cup is a sporting event that is highly awaited by many people because football is a popular sport around the world. Many countries are reaping the pros and cons of the 2018 FIFA World Cup held by Russia, especially the ability of Russia to become the host mega sports events. This research was conducted by using a library research method where data and information were obtained from relevant sources of the problems by this research. The study will be analyzed with the perspective of realism, the theory of Jackson & Sorensen. The concept of national interest was brought by Donald E. Nuechterlein. The results of the research show that Russia has a national interest to be achieved by hosting the 2018 FIFA World Cup. In terms of economy, The Russian government hopes that Russia will achieve the interests of either profit or revenue from tourist visits during the world cup and make Russia be a tourist destination of the country. In terms of politics, the government wants to increase the prestige of the country successfully. This opportunity was also used by the President of Russia, Vladimir Putin to improve his good image during his tenure in Russia. Keywords : National Interest, World Cup, FIFA, Russia